Thinking Muhammad Legenhausen's non-reductive pluralism through: some reflections about its implications - Bigliardi, Stefano (Universiti Kebangsaan Malaysia, 2014)
One of the most vibrant contemporary philosophical debates concerns the definition, and defence, of religious pluralism. The philosophers who address such a topic usually hold widely divergent views regarding its exact definition and the arguments through which it can be upheld. The absence of a general consensus notwithstanding, the debate on religious pluralism has ‘de facto’ become an important area of dialogue between different religions in general, and between Christianity and Islam in particular. At stake in the present paper is the discussion of pluralism developed by the US-American-Persian philosopher Muhammad (Gary Carl) Legenhausen (b. 1953), that he presents as a criticism of the views of the late British theologian John Harwood Hick (1922-2012). Hick developed his views mainly influenced by Christianity, yet he also took into account some ideas advanced by Muslim authors. Legenhausen, a convert to Islam, puts forth his own version of pluralism in the framework of a discussion of the concept as it has emerged within Christianity, and advances a refutation of Hick's view complementary to his own theory of pluralism. The aim of the present pages is to offer an overview of Legenhausen’s contribution and discuss some of its possible implications and premises. In other words, rather than producing a defence of Legenhausen’s theory, this study is to analyse the logic behind and beyond his specific ‘Muslim proposal’ and explain what some of its unstated premises might be, as well as the consequences of fully embracing such stance, for philosophers, – not only Muslims ones –, interested in understanding religion from a religious point of view and in advocating that religious differences should not turn into a reason of animosity. The paper is divided into two main sections. The first one reconstructs Legenhausen's version of religious pluralism, while especially recalling the points with which it is presented as clashing with Hick's one. The second section is dedicated to the critical assessment.